Hospital-based integrative medicine : a case study of the barriers and factors facilitating the creation of a center - Coulter, Ian D., 1945- (Rand Corporation monograph series., 2008)
This study tracks the establishment of a single hospital-based integrative medicine center. Although some factors clearly worked in favor of the center, the hospital had few models to guide it and no experience in creating such a clinic. Thus, it made many decisions in the areas of administration, finance, and legal issues that created barriers to the center's success, and the center was ultimately closed.